2014
DOI: 10.7860/jcdr/2014/9207.4671
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Analgesic Activity of Guduchi (Tinospora Cordifolia) Using Animal Model

Abstract: Introduction: Pain is a very well-known signal of ill health and analgesics are the drugs that are used to relieve pain. The main problem with these drugs remains that of side effects. Safer alternatives are natural herbs. Guduchi (Tinospora cordifolia) is one such plant with analgesic potential but few studies are there.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 6 publications
1
11
0
1
Order By: Relevance
“…Anti-inflammatory effects of T. cordifolia were also detected in autoimmune arthritis mediated by decreased synthesis of proinflammatory cytokines, for example, IL-1β, IL-17, tumor necrosis factor-α, and IL-17 ( Sannegowda et al., 2015 ). Some data also suggest that T. cordifolia can mediate the peripheral and central nervous system mechanisms and exert analgesic effects ( Goel et al., 2014 ). In addition, T. cordifolia has antipyretic effects against fever ( Pushpangadan et al., 2006 ).…”
Section: Promising Pharmacological Activities Of Guduchi ( mentioning
confidence: 99%
“…Anti-inflammatory effects of T. cordifolia were also detected in autoimmune arthritis mediated by decreased synthesis of proinflammatory cytokines, for example, IL-1β, IL-17, tumor necrosis factor-α, and IL-17 ( Sannegowda et al., 2015 ). Some data also suggest that T. cordifolia can mediate the peripheral and central nervous system mechanisms and exert analgesic effects ( Goel et al., 2014 ). In addition, T. cordifolia has antipyretic effects against fever ( Pushpangadan et al., 2006 ).…”
Section: Promising Pharmacological Activities Of Guduchi ( mentioning
confidence: 99%
“…These results show that this extract possess a significant analgesic activity in Hot Plate Test. 17 Hussain et al showed increase in mean latency time of tail flick (sec) in extract treated group in comparison with control group using mice as experimental animal and tramadol as standard drug in both tail flick and hot plate test. 18 Siddhalingappa et al also found out that T. cordifolia aqueous extract significant increase in the reaction time (pain threshold) in doses of 100 mg/kg, 200 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…18 Bhomik et al has shown administration of this T. cordifolia extract orally and pentazocine intraperitoneally significantly reduce writhes counts (p<0.001 and p<0.001 respectively) when compared with the control group in sodium chloride (NaCl) induced abdominal writhing method using rats as experimental animal. 17…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al (2010) (Phondani et al, 2010). Sahoo et al (2001) menyatakan bahwa poli herbal yang mengandung Tinospora dapat meningkatkan performa ternak, daun berkasiat sebagai analgesik (Goel et al,2014), serta dapat mengatasi penyakit kulit (Tariq et al, 2014).…”
Section: Daun Sembukanunclassified